The modern look on the platinum-based chemotherapy effectiveness the modern look on the platinum-based chemotherapy effectiveness - Rybin, A. (Journal of Education, Health and Sport, 2025)
The aim of the work is to assess the quality of life in platinum-resistant patients with ovarian cancer, depending on the degree of pharmacoresistance and differentiated use of chemotherapy. Materials and methods. The study was conducted on the basis of the University Clinic of the Odessa National Medical University during 2014 - 2020 years. 350 patients with adenocarcinoma of the ovaries of III-IV stage were examined, who performed cytoreductive operations. Results and discussion. It is shown that the initial values on the subscales of the questionnaires EORTC QLQ-C30 and FACT-G in patients classified as different clinical groups were compared. When using a differentiated approach in the treatment of patients with OC, the indicators on the scales of physical (PF), role (RF) and emotional functioning (EF) were significantly improved. In addition, the intensity of nausea (NV) and general weakness (FA) decreased in patients of groups III and IV. In the case of differentiated use of chemotherapeutic agents with metabolic support, the total score according to the FACT-G questionnaire was 77.8±0.9 points in group III, and 77.9±0.8 points in group IV, which significantly exceeds the received in I and II groups - 72.2±1,2 and 71,6±0,9 points. The described differences were kept throughout the period of catamnestic observation. Conclusions: The use of a differentiated approach in the treatment of patients with RI significantly improved indicators on the scales of physical (PF), role (RF) and emotional functioning (EF). After treatment, the intensity of nausea (NV) and general weakness (FA) decreased in patients of groups III and IV. The described differences were retained for 12 months after the completion of the course of treatment. Prospects for further research are related to the study of the dynamics of life quality of patients with OC at the subsequent stages of catamnestic observation.